2022
DOI: 10.1364/oe.453946
|View full text |Cite
|
Sign up to set email alerts
|

Noise-like pulse generation and amplification from soliton pulses

Abstract: The evolution of soliton pulses into noise-like pulses in a nonlinear fiber externally to the laser oscillator is demonstrated at 1.9 µm, for the first time. Soliton collapse based mechanisms induce noise-like pulses with varying properties as a function of nonlinear fiber length without requiring any laser cavity feedback. The proposed method allows the generation of noise-like pulses with a sub-300 fs spike and sub-40 ps pedestal duration. Power scaling of the noise-like pulses is demonstrated in a double-cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Under strong pumping, as the pump power increases, the nonlinear effect is enhanced and the spectrum is gradually broadened (Figure 4c). [36,37] The 20 dB spectral bandwidth reaches ≈77 nm initially. With increasing pump power, the maximum spectral bandwidth reaches ≈142 nm (Figure S6a, Supporting Information).…”
Section: All-fiber High-power Stml Oscillatorsmentioning
confidence: 99%
“…Under strong pumping, as the pump power increases, the nonlinear effect is enhanced and the spectrum is gradually broadened (Figure 4c). [36,37] The 20 dB spectral bandwidth reaches ≈77 nm initially. With increasing pump power, the maximum spectral bandwidth reaches ≈142 nm (Figure S6a, Supporting Information).…”
Section: All-fiber High-power Stml Oscillatorsmentioning
confidence: 99%
“…The inverse process is equally interesting, i.e. efficient transformation of conventional unstructured pulses into noise-like ones [51]. Development of effective methods of conversion from sub-pulse packets into 'normal' pulses and vice versa is important for full realisation of the potential possessed by noise-like pulses…”
Section: Conversion Of Noise-like Pulses Into 'Conventional' Ones And...mentioning
confidence: 99%
“…Recently, it has been demonstrated that NLPs can be generated externally to a laser cavity [14][15][16][17]. For example, Stokes waves NLPs that have a wavepacket width of 3.7 ps, an average temporal width of 14.7 fs for the inner structures, and an average power of 5 W are generated by launching optical pulses into a fiber amplifier with a positive GVD [17].…”
Section: Introductionmentioning
confidence: 99%
“…The Stokes waves NLPs are generated due to intrapulse SRS and spontaneously scattered noise. In addition, NLPs at 1.89 µm wavelength that have a temporal width of 38.11 ps for the wavepacket and an average temporal duration of 150 fs for the inner structures are generated by amplifying the output pulses from a highly nonlinear fiber [14]. It is also found that NLPs can be generated through a fiber amplifier that consists of a single-mode fiber (SMF) with a negative GVD [1,15].…”
Section: Introductionmentioning
confidence: 99%